Vocational education and training in Slovakia : short description - (:unkn) unknown (Publications Office of the European Union, 2016)
This overview of the vocational education and training (VET) system in Slovakia is published during the Presidency of the Slovak Republic in the Council of the EU (second half of 2016). It provides an insight into the main features of the Slovak VET system and highlights recent VET policy developments. "The Slovak economy is largely driven by manufacturing and could benefit from more diversification to make it less sensitive to economic shocks and more skill-intensive jobs, encouraging innovation. VET has traditionally played a strong role, responsible for around two-thirds of graduates at upper secondary level. But qualifications do not always match labour market needs. A 'dual' VET scheme was introduced in 2015/16 as one way to address mismatch. First results show greater involvement of employers in VET: it is now in their interest to attract learners and to deliver job-relevant training. The government also intends to promote VET at higher levels to make it more attractive." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 4.1 Finanzierungsquellen; S 4.3 Steuerung; P 3.2 Lehrpersonal; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Duales System; Berufliche Weiterbildung; Bildungsfinanzierung; Bildungssteuerung; Bildungspersonal; Curriculumentwicklung; Anrechnung von Bildungsleistungen; Qualitätssicherung; Slowakei